A Flexible Encapsulation Structure for Ambient‐Air Operation of Light‐Emitting Electrochemical Cells1. Issue 1 (26th June 2015) - Asadpoordarvish, A.; Sandström, A.; Edman, L.
Abstract : The emerging field of organic electronics is heralded because it promises low‐cost and flexible devices, and it was recently demonstrated that a light‐emitting electrochemical cell (LEC) can be fabricated with cost‐efficient methods under ambient air. However, the LEC turns sensitive to oxygen and water during light‐emission, and it is therefore timely to identify flexible encapsulation structures. Here, we demonstrate that a multilayer film, featuring a water and oxygen barrier property of ≈1 × 10 –3 g/m 2 /day and ≈1 × 10 –3 cm 3 /m 2 /bar/day respectively, is fit for this task. By sandwiching an LEC between such multilayer barriers, as attached by a UV‐curable epoxy, we realize flexible LECs with performance on par with identical glass‐encapsulated devices, and which remain functional after one year storage under air. Abstract : We report the fabrication and ambient‐air performance of flexible light‐emitting electrochemical cells (LECs). A flexible LEC sandwiched between multilayer barriers, featuring a water and oxygen barrier property of ≈1 × 10 −3 g/m 2 /day and ≈1 × 10 −3 cm 3 /m 2 /bar/day respectively, and as attached together with UV‐curable epoxy, performs on par with identical glass‐encapsulated devices. Such a flexible LEC also remains functional after one year storage under ambient air.